P–561 Male and female blastocyst: any difference other than the sex?. (6th August 2021) - Carrasc. Canal, B; Pons, M C; Parriego, M; Boada, M; García, S; Polyzos, N P; Veiga, A
Abstract: Study question: Is there any imbalance in the sex ratio (SR) and in the aneuploidy rate of male and female human blastocysts from a PGT-A programme? Summary answer: Although SR in human blastocysts is significantly male-biased, more aneuploidies are observed among male blastocysts, resulting in comparable euploid male and female embryos available. What is known already: More boys than girls are born worldwide, meaning that the SR at birth is biased towards males. Differences in the SR of children born after ART have been also reported. Factors such as the insemination technique or the day of embryo transfer have been shown to be related to the SR at birth, but whether the SR is shifted during the preimplantation and/or postimplantation development remains unknown. Study design, size, duration: Embryos from patients undergoing 921 PGT-A cycles from September 2017 to February 2020 were included in the study. Data from the chromosomal constitution of 2637 biopsied blastocysts was retrospectively analysed. Participants/materials, setting, methods: Embryos were cultured in time-lapse incubators with low oxygen tension (5%) (Embryoscope®; Geri®) using single-step medium (Global®, LifeGlobal®; GTL™, Vitrolife). Blastocyst biopsy was performed between D5-D7 followed by immediate vitrification (Cryotop®, Kitazato). Trophectoderm samples were analysed by NGS. Embryos were categorized as euploid, aneuploid or mosaic. Embryos were called as mosaic when the deviation from the normal copy number was ≥30% and <70%. Main results and the role of chance: Overall biopsies from 2637 blastocysts were analysed, 1320 on day 5 (50.1%), 1169 on day 6 (44.3%) and 148 on day 7 (5.6%). Sex distribution among the embryos analysed was skewed in favor of male sex with 1401 diagnosed as male (53.1%) and 1236 were female (46.9%), [OR (95%CI):1.13(1.05–1.22)]. As a consequence of this biased SR, more male embryos reached the blastocyst stage and were biopsied both on day 5/6 (708/1320, 53.6% on day 5 and 619/1169, 53% on day 6). Embryos biopsied on day 7 were balanced between sexes with 50% being male and 50% being female. Following biopsy and PGT-A, 1086 (41.2%) of the embryos were classified as euploid, 1349 (51.16%) as aneuploid, and 202 (7.7%) as mosaic embryos. More chromosomal anomalies were observed among male blastocysts when compared to the female ones, 738 (52.7%) vs 611 (49.4%). Similarly, mosaicism was more frequents in male as compared with female blastocysts, 123 (8.8%) vs 79 (6.4%). (P = 0.000). As more aneuploidies are observed among male blastocysts, the final number of available euploid blastocysts for embryo transfer was comparable between sexes (540 male/546 female), [OR (95%CI): 0.99 (0.87–1.11)]. Limitations, reasons for caution: This is a retrospective study. Only embryos at the blastocyst stage have been analyzed. Potential confounding factors such as sperm quality or the female age have not been analyzed. No data regarding the SR at birth have been analyzed in these study. Wider implications of the findings: In our study, more male embryos develop to the blastocyst when compared to female ones. It can be hypothesized that female embryos can be more affected by an early arrest at cleavage stages. SR at birth would be expected to be similar as more aneuploidy is observed in male embryos. Trial registration number: Not applicable